ESTRATEGIAS REGIONALES DE GESTIÓN AMBIENTAL. EL CASO DEL PROYECTO MINERO LAS BAMBAS DE APURÍMAC - Espinoza Herrera, Nemesio (2006)
Objetive: The study has as purpose the evaluation of incidences in mining activity in regional ecology and to propose an enviromental management strategy. Method: We have been visited the Las Bambas mine located in Apurimac as well as the surrouding communities such as Tambopata, Challhuahuacho, Progreso y Chuquibambilla, places that are located in the provinces of Cotabambas and Grau respectively. It has been interviewed the provincial majors of Cotabambas and Grau. Similarily, deeply interviews to the community people have been done . Through the visits it has been made observations related to the reality. Results: In the Apurimac region there are evidences of enviromental contamination and is foreseeable that the mining operations of the project Las Bambas will worsen the problem. As there is not a regional strategy of enviromental management it will cause a great risk to the existing biodiversity. Conclusion: Being necessary the mining processes in order to promote the social and economic development of the region labeled as extreme poverty, the region of Apurimac requires the establish of a regional strategy for environmental management.